New Qualification Level Description in Malaysian Framework for Equivalence Checking Via APEL Process - Kaprawi, Noraini; Saparwan, Norfaezah; Mohd Amin, & Noor Farhah Muzaimah (Journal of Technical Education and Training, 2019)
Accreditation of Prior Experiential Learning (APEL) is a systematic process involving the identification, documentation and assessment of learning based on previous experience. This study is aimed at determining the descriptions of each qualification level within the Malaysian Qualifications Framework (MQF) that can be proposed for use in the research of equivalence between skill and academic of the APEL process. Through this equity research, it can facilitate individual passage from skills to further higher education in the academic. This study used a qualitative approach which involved exploratory methods through document analysis (Malaysian Qualification Framework, Australia Qualification Framework and Europe Qualification Framework)  interviews (semi structure) and descriptive survey (score mean and standard deviation) methods through a questionnaire instrument. Based on the information obtained from UTHM, ADTEC, KKTM and IKBN the total population of this study is 97 persons. However, only 54 respondents gave feedback on distributed surveys. The findings show that all description items of each level of qualification proposed in the MQF are best suited to describe learning outcomes for each level. A description that includes three domains (knowledge, skills and competence) can be suggested to stakeholders. This will help individuals from areas of skills to pursue higher education in the academic field through the APEL process.